2012
DOI: 10.1016/j.jviromet.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating platelet–monocyte complexes in persons infected with human immunodeficiency virus type-1

Abstract: Activated platelets form transient aggregates with monocytes in circulation and have a half-life of approximately 30–60 minutes. These complexes are increased in various inflammatory conditions and are an early marker of myocardial infarction. HIV-1 infection is associated with chronic inflammation, and increased CD16+ inflammatory monocytes have been observed in these individuals, probably as a result of increased interaction with platelets. However, narrow detection period and platelet activation during samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 25 publications
5
61
0
1
Order By: Relevance
“…158,159 Furthermore, platelet-monocyte aggregates are greatly increased in the circulation of both infected primates and humans, and platelets may induce monocyte differentiation into a more inflammatory phenotype. 159,160 Thrombocytopenia is associated with increased neurologic complications of HIV infection, and neuro-HIV is hypothesized to be driven by infected macrophage migration into the brain. 158,160,161 This has led some to speculate that a platelet-induced macrophage inflammatory phenotype may accelerate neurologic complications of HIV infection, but much remains to definitively demonstrate this.…”
Section: Platelets and Infectious Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…158,159 Furthermore, platelet-monocyte aggregates are greatly increased in the circulation of both infected primates and humans, and platelets may induce monocyte differentiation into a more inflammatory phenotype. 159,160 Thrombocytopenia is associated with increased neurologic complications of HIV infection, and neuro-HIV is hypothesized to be driven by infected macrophage migration into the brain. 158,160,161 This has led some to speculate that a platelet-induced macrophage inflammatory phenotype may accelerate neurologic complications of HIV infection, but much remains to definitively demonstrate this.…”
Section: Platelets and Infectious Diseasementioning
confidence: 99%
“…159,160 Thrombocytopenia is associated with increased neurologic complications of HIV infection, and neuro-HIV is hypothesized to be driven by infected macrophage migration into the brain. 158,160,161 This has led some to speculate that a platelet-induced macrophage inflammatory phenotype may accelerate neurologic complications of HIV infection, but much remains to definitively demonstrate this. Influenza also exerts a large public health impact every year.…”
Section: Platelets and Infectious Diseasementioning
confidence: 99%
“…However, other groups have reported that the formation of MPA is primarily dependent on platelet activation and to a lesser extent on monocyte activation. 26,44,45 Therefore, we speculated that the increased monocyte activation in HIV-1 infection might be partially ascribed to MPA formation, which rendered monocytes more active, more adhesive, more procoagulant, and more inflammatory through the release of pro-inflammatory cytokines (such as IL-6 and tumor-necrosis factor-a) or the expression of tissue factor, resulting in an increased CVD risk. In summary, we showed for the first time that MPA levels are increased on CD14 …”
Section: Cd16mentioning
confidence: 99%
“…Increased MPA formation was previously reported in HIV-1-infected patients receiving antiretroviral therapy and in simian immunodeficiency virus infection. 25,26 However, the MPA levels in HIV-1-infected, treatment naive patients and the changes in MPA levels as the disease progresses have not been previously examined. Although monocyte activation is a typical characteristic of HIV-1 infection, the association between monocyte activation and MPA levels in HIV-1 infection is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Uma possível explicação para este problema seria a formação de agregados de plaquetas e monócitos, frequente nos indivíduos infectados pelo HIV (179) e que dificultaria o processo de separação dos monócitos das outras células, feito por aderência em superfície plástica. Outro fenômeno observado foi a apoptose precoce dos monócitos em cultura o que poderia estar relacionado ao grau de ativação celular do indivíduo infectado, levando à morte celular induzida por ativação (activation-induced cell death) (180)(181)(182) .…”
Section: Discussionunclassified